Meta-Analysis: Qualitative Review of Human Resource Management Studies - Gemechu Tufa; Shashi Kant; Gemechu Nemera Dinber (Advanced Qualitative Research, 2023)
This articlse defines a systematic qualitative review and considers how it can advance our knowledge of HRM literature. Those of us who care about people who are in Human Resource Management (HRM) literature rely on data demonstrating the efficacy of various interventions. In order to inform our practice and better understand what works, a solid systematic review can be quite helpful in compiling research evidence. Understanding how people with HRM literature experience their HRM literature and their treatment, in addition to having proof of effectiveness, can be helpful when we are collaborating with them to deliver care that satisfies their requirements. A thorough qualitative systematic review can also produce new insights, frequently illuminating the HRM studies' contribution to literature and can aid in the development of theories. Such a review can provide insight into what like to have long-term HRM literature. The many steps of meta-ethnography, the most popular methodology used for qualitative systematic reviews, are presented in this article. It provides examples of the kinds of discoveries that can result from this method using data from four meta-ethnographies that are pertinent to HRM literature. It demonstrates how new insights could develop and provides an illustration of how chronic musculoskeletal HRM literature can be felt as "an antagonistic fight" in many facets of a person's life. The conclusion of this article is that evidence from qualitative systematic reviews can be used in conjunction with or as a complement to evidence from more quantitative methodologies.